Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376840
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eye Gaze in Security and Privacy Applications: Survey and Future HCI Research Directions

Abstract: For the past 20 years, researchers have investigated the use of eye tracking in security applications. We present a holistic view on gaze-based security applications. In particular, we canvassed the literature and classify the utility of gaze in security applications into a) authentication, b) privacy protection, and c) gaze monitoring during security critical tasks. This allows us to chart several research directions, most importantly 1) conducting field studies of implicit and explicit gaze-based authenticat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 188 publications
(309 reference statements)
2
57
0
Order By: Relevance
“…The security of graphical passwords can be improved by, for example, using contactless input for, such as eye gaze or mid-air gestures. Indeed, one direction to address thermal attacks is to employ schemes that use modalities that do not leave heat traces [9,10,14,19]. An alternative could be to use cue-based authentication where the user's input depends on system cues [7,20,25,27].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…The security of graphical passwords can be improved by, for example, using contactless input for, such as eye gaze or mid-air gestures. Indeed, one direction to address thermal attacks is to employ schemes that use modalities that do not leave heat traces [9,10,14,19]. An alternative could be to use cue-based authentication where the user's input depends on system cues [7,20,25,27].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Also, Kumar et al presented in [23] a Gaze-Based password entry approach in order to prevent the shoulder-surfing attack. A survey on gaze-based security applications was carried out in [24] that discussed a set of opportunities as well as challenges. Likewise, the gazebased application is reviewed in [25] and classified into three categories: authentication, privacy, and gaze monitoring.…”
Section: Related Workmentioning
confidence: 99%
“…A recent survey on eye gaze for security and privacy applications [Katsini et al 2020] showed that gaze is promising for password entry. In addition to usability benefits, gaze is subtle and hard to observe, and can be a powerful means to add biometrics as a layer on top of gaze-based passwords.…”
Section: Related Workmentioning
confidence: 99%
“…This resulted in an understanding of how strong the TouchLockPatterns users create are, common pitfalls, and areas of improvement. At the same time, advances in gaze estimation accuracy and eye tracking hardware led to gaze gaining popularity for authentication as a more natural and secure modality for entering passwords [Katsini et al 2020]. Gaze offers usability advantages Figure 1: Study setup where we investigate the difference between using gaze and touch for entering lock patterns over traditional modalities such as touch and pointing (e.g., mouse) and its subtleness makes it more secure against observation attacks.…”
Section: Introductionmentioning
confidence: 99%